2021
DOI: 10.1111/1365-2745.13603
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variations in leaf traits, productivity and resource use efficiencies in the dominant species of subalpine evergreen coniferous and deciduous broad‐leaved forests along the altitudinal gradient

Abstract: Many studies have reported intraspecific variations in leaf functional traits, but their contribution to plant performance and ecosystem function are poorly understood. We studied altitudinal gradients of intraspecific variations in leaf traits, productivity and resource use efficiency in the dominant species of subalpine evergreen coniferous and deciduous broad‐leaved forests in Japan. We addressed three hypotheses, which are exclusive to each other. (1) Leaf traits vary along the leaf economics spectrum (LES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 72 publications
0
17
1
Order By: Relevance
“…The result is reinforced by the fact that leaf δ 13 C (water use efficiency, Farquhar et al 1989) was significantly different among altitudes, with the greates values at 3200 m, suggesting that plants show acclimation to drying by freezing and low temperature at subalpine treelines in spite of greater water availability (Li et al 2004). Hikosaka et al (2021) showed that leaf N based on the area in Fagus crenata increases at higher altitudes, whereas leaf N did not change with increasing altitude in the present study, indicating that N limitation may not play a key role in the growth of A. fargesii at treeline. In our study, main stem diameter showed an increasing trend with increasing altitudes, but there was a reduction in tree height with increasing altitudes, which might be due to the low temperature that suppressed meristematic growth of primary meristems (Körner 2003).…”
Section: Water Relations Tissues Non-structural Carbohydrate and Morp...contrasting
confidence: 72%
“…The result is reinforced by the fact that leaf δ 13 C (water use efficiency, Farquhar et al 1989) was significantly different among altitudes, with the greates values at 3200 m, suggesting that plants show acclimation to drying by freezing and low temperature at subalpine treelines in spite of greater water availability (Li et al 2004). Hikosaka et al (2021) showed that leaf N based on the area in Fagus crenata increases at higher altitudes, whereas leaf N did not change with increasing altitude in the present study, indicating that N limitation may not play a key role in the growth of A. fargesii at treeline. In our study, main stem diameter showed an increasing trend with increasing altitudes, but there was a reduction in tree height with increasing altitudes, which might be due to the low temperature that suppressed meristematic growth of primary meristems (Körner 2003).…”
Section: Water Relations Tissues Non-structural Carbohydrate and Morp...contrasting
confidence: 72%
“…Higher SLA and N concentration modulate a faster resource acquisition at lower elevation than at higher elevation with decreasing leaf N concentration and SLA, consequently altering the primary productivity (Reich, 2014). It was also supported by studies along elevation gradients (Hikosaka et al, 2021) and in tropical and temperate forests (He et al, 2019). Functional trait diversity is considered as an integrative metric to explore GPP from tropical to cold-temperate forests in Eastern China (Li, Hou, et al, 2022).…”
Section: Trait Variation and Ecosystem Productivitymentioning
confidence: 87%
“…Traits related to plant morphology, physiology and phenology influence the fitness of species (Niu et al, 2018; Read et al, 2014), and reflect adaptive responses to abiotic and biotic conditions (Kattge et al, 2011; Midolo et al, 2019). Moreover, trait divergence can also be used to gain insights into functional ecology and biogeography (Bolnick et al, 2011; Kattge et al, 2011; Reichstein et al, 2014), ecosystem productivity (Cui et al, 2019; Hikosaka et al, 2021), reproductive phenology (Liu et al, 2021), patterns of biodiversity (Li, Liu, et al, 2022; Violle et al, 2012), water–energy dynamics (Blonder et al, 2020; Lu et al, 2022; O'Brien, 2006) and responses to climate change (Li et al, 2020; Westerband et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…There were significant spatial differences in NPP of different grassland types, and the NPP of AM was significantly higher than that of DS. Significant differences in NPP were closely related to habitat heterogeneity (Hikosaka et al, 2021). Due to the differences in biological or abiotic factors in different regions, there are significant differences in NPP of grassland in different regions (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Leaf traits are widely used to detect the adaptability of plants to the living environment (Hikosaka et al, 2021). The traits we selected included LA, SLA, LDMC, LN, LP, and leaf N/P ratio.…”
Section: Community Leaf Traits Datamentioning
confidence: 99%